Folate-Decorated Nanogels for Targeted Therapy of Ovarian Cancer - Nukolova, Natalia V. (2011)
Nanogels are comprised of swollen polymer networks and nearly 95 % water and can entrap diverse chemical and biological agents for cancer therapy with very high loading capacities. Here we use diblock copolymer poly(ethylene oxide)-b-poly(methacrylic acid) (PEO-b-PMA) to form nanogels with the desired degree of cross-linking. The nanogels are further conjugated to folic acid (FA) and loaded with different types of drugs (cisplatin, doxorubicin). For the first time we demonstrate a tumor-specific delivery and superior antitumor effect in vivo of an anti-cancer drug using these polyelectrolyte nanogels decorated with folate targeting groups. This reinforces the use of nanogels for the therapy of ovarian and other cancers, where folate receptor (FR) is over-expressed.